Community-Acquired Pneumonia in Children Caused by Pneumococci of MLSB- and M-Phenotype: Clinical Cases - Natalya A. Ilenkova; Irina N. Protasova; Elena S. Sokolovskaya (Вопросы современной педиатрии)
The key to effective treatment of a bacterial infection is a rapid and proper selection of antimicrobial therapy. WHO and UNICEF developed the Global Action Plan for the Prevention and Control of Pneumonia and Diarrhoea (GAPPD) aimed to elimination of the preventable causes of child death by 2025 by optimizing diagnosis and treatment. The main pneumonia agents are fastidious microorganisms that require special nutrient media and cultivation conditions that are absent in many laboratories. Due to low effectiveness of the etiological diagnosis, the choice of antibiotic therapy for pneumonia in the practice of a pediatrician is usually empirical. The article describes clinical cases of community-acquired pneumonia in children caused by strains of Streptococcus pneumoniae with a multiple antibiotic resistance. The above experience can be used by pediatricians in everyday practice.